Investigating the Effective Components of Institutional Challenges of Citizen Participation in Sustainable Urban Regeneration Case Study: Tabriz City - nazli pakro; dariyosh Sattarzadeh (تحقیقات کاربردی علوم جغرافیایی)
the purpose of the present study is to examine the effective factors in the institutional challenges of citizen participation in sustainable urban regeneration in Tabriz city. The present research is developmental-applied regarding the purpose and methodologically hybrid which uses both qualitative and quantitative methods. The study population was selected for interviewing among managers and experts from organizations related to the subject of research. To analyze the quantitative findings, the spss22 software and the NVivo10 software were used to analyze the field interviews. The results of this study indicate that Tabriz city faces significant institutional challenges in the area of sustainable urban regeneration, though it is possible to increase the participation of citizens in urban regeneration projects, and take a step towards meeting these challenges through utilizing institutional components of effective citizen participation in urban regeneration, changing the view of authorities towards capacity and the capabilities of NGOs, the establishment and development of NGOs in relation to urban renewal and regeneration and the removal of legal barriers associated with NGOs can.